Encyclopedia of Analytical Chemistry 2000
DOI: 10.1002/9780470027318.a2003
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy in Analysis of Polymers

Abstract: Atomic force microscopy (AFM), in which a sharp probe is employed for profiling surfaces with unique resolution, has developed into an invaluable multidisciplinary technique for advanced characterization of polymer materials. In its basic function, AFM provides high‐resolution imaging of surface structures between the scales of a few nanometers to hundreds of micrometers. This capability is useful for quantitative analysis of surface microroughness of technological surfaces with high sensitivity and accuracy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 61 publications
0
54
0
Order By: Relevance
“…The distance between the extending and retracting friction curves is a qualitative measure of the friction between the probe and the surface. 36 Surface friction measurements were conducted at a fixed scan rate of 1 Hz, consistent with methods commonly reported in the literature for polymer samples. 30,36 POSS nanocomposites exhibit reduced relative friction in comparison to the neat polymer, with friction decreasing as a function of increasing POSS concentration.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The distance between the extending and retracting friction curves is a qualitative measure of the friction between the probe and the surface. 36 Surface friction measurements were conducted at a fixed scan rate of 1 Hz, consistent with methods commonly reported in the literature for polymer samples. 30,36 POSS nanocomposites exhibit reduced relative friction in comparison to the neat polymer, with friction decreasing as a function of increasing POSS concentration.…”
Section: Resultsmentioning
confidence: 92%
“…In same cantilever is employed to obtain the measurements. 30,36,38 The samples were imaged in tapping mode after LFM measurements to ensure that surfaces were not damaged during the friction studies, and no artifacts were observed on the images. Additionally, AFM probes were imaged via SEM after surface friction measurements to ensure that there were no visible changes to the geometry of the probe during scanning.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the AFM imaging parameters and tip sharpness are pivotal, interactions. 43 However, resolution was greatly enhanced during imaging of polymer samples by hard tapping applying a considerably decreased A sp /A o ratio. 43,47 Tip-sample force interactions are dependent on the sharpness and overall shape of the AFM probe.…”
Section: Methodsmentioning
confidence: 99%
“…43 However, resolution was greatly enhanced during imaging of polymer samples by hard tapping applying a considerably decreased A sp /A o ratio. 43,47 Tip-sample force interactions are dependent on the sharpness and overall shape of the AFM probe. Commercial AFM probes can be dull or can become dull during imaging due to wear or contamination with debris.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation